Pengaruh Terapi Kepalan Bola dalam Peningkatan Kemampuan Fungsi Saraf pada Penderita Stroke Iskemik - Riza Ratna Listi (Yayasan Literasi Sains Indonesia, 2024)
Functional disorders, also known as strokes, are conditions when blood flow to the brain is blocked and cannot reach the brain cells, resulting in paralysis of the nerves (neurological deficit) and even death. Stroke is a clinical symptom of loss of function of the central nervous system that develops and attacks quickly. The uncontrollability of nerve signals to the muscles is caused by damage to parts of the brain. As you get older, you are at risk of having a stroke. Judging from the cause, strokes are divided into two types, including hemorrhagic strokes which are caused by rupture of cerebral blood vessels, while ischemic strokes are caused by thrombus or embolism in the cerebral blood vessels. The causes of stroke consist of factors that can be changed and factors that cannot be changed. This study aims to determine the effect of ball fist therapy on improving the ability of nerve function in the upper limbs. Literature review is the method used in preparing this research. Literature reviews are carried out on research articles, journals, books and other sources. The results stated that there was an increase in the ability of nerve function in the upper limbs after ball fist therapy was carried out for approximately one month with routine ball fist therapy in stroke patients.the contents of this template, please backup it first.